Permeation of sodium dodecyl sulfate through polyaniline-modified cellulose acetate membranes - Valente, A. J. M. (2005)
The preparation of polyaniline (PANi)-cellulose acetate (CA) blends by casting films from a suspension, is reported. Two membranes were prepared from different solvents, one with a homogeneous and the other a heterogeneous dispersion of PANi in CA matrices. The membranes were characterized by X-ray diffraction, SEM, DSC, and FTIR, and the results were compared with those obtained for pure CA and PANi films. The transport properties of water and sodium dodecyl sulfate (SDS) in membranes of the PANi-CA blends and of CA were analysed. The transport of SDS and water depends on both the bulk/polymer density and the PANi content. In the homogeneous blend, the interaction between SDS and the polymer plays an important role in the transport mechanism. An irreversible interaction is observed, which can be monitored by UV-vis spectroscopy. The spectra of homogeneous, highly transparent PANi-CA blends show a pronounced sensitivity to SDS concentration, with detection limits [SDS]>=0.1 mM for films with a PANi concentration of 0.05% w/v.